Cholesterol diet and effect of long-term withdrawal on plaque development and composition in the thoracic aorta of New Zealand White rabbits - Riedmüller, Karen; Metz, Stephan; Bonaterra, Gabriel A.; Kelber, Olaf; Weiser, Dieter; Metz, Jürgen; Kinscherf, Ralf (Atherosclerosis, 2010)
Aims - Experimental study on plaque progression, regression and composition in atherosclerotic thoracic aorta of hypercholesterolemic rabbits after long-term withdrawal of cholesterol-enriched diet (CED). - Methods - Rabbits were fed 2% cholesterol for 6 weeks followed by withdrawal periods for 15, 23, 34, 68, or 78 weeks. Cholesterol, triglyceride, and phospholipids levels in blood and cholesterol concentrations in aorta were quantified. Plaque size and cellularity, phenotype of macrophages and smooth muscle cells were (immuno)histomorphometrically analyzed in segments of the thoracic aorta. - Results - After 6 weeks of CED, blood cholesterol levels were about 80-fold higher, whereas atherosclerosis and cholesterol content in the thoracic aorta were only minimally increased. However, the latter significantly increased within 15 weeks after cholesterol withdrawal, while serum cholesterol level was still 10-fold increased. Thereafter plaque area and cholesterol content remained almost unchanged until the end of the study despite a long-term normalization of serum cholesterol level after withdrawal of CED. Directly after 6 weeks of CED the densities of macrophages and apoptotic cells within plaques were highest, decreasing after cholesterol withdrawal, whereas, vice versa the density of smooth muscle cells (SMCs) significantly increased. - Conclusion - We suggest that atherosclerotic plaques respond to long-term withdrawal of CED by decrease in number and phenotype of macrophages and increase of SMCs without regression of the lesion size. The cellular changes are suggested to considerably contribute to higher plaque stability.